2016
DOI: 10.1039/c6ra05814k
|View full text |Cite
|
Sign up to set email alerts
|

A new bisglycolamide substituted calix[4]arene-benzo-crown-6 for the selective removal of cesium ion: combined experimental and density functional theoretical investigation

Abstract: A new bisglycolamide substituted calix-benzo-crown-6 (CBCBGA) ionophore has been synthesized and characterized by using 1 H, 13 C NMR, ESI-MS and elemental analysis. Detailed investigations on the effect of various parameters such as the aqueous phase acidity, ionophore concentration and nitrate ion concentration on extraction of cesium have been carried out. The new ionophore is found to be highly selective for Cs over other metal ions present in the simulated high level liquid waste solution. The complexing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 36 publications
2
6
0
Order By: Relevance
“…The results imply that CBCBGA is highly efficient for Cs + over the other metal ions. These results also indicate that the selectivity of the metal ions for CBCBGA decreases with the decreasing size of the metal ions in the following order: Cs + > Rb + > K + > Na + . , …”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…The results imply that CBCBGA is highly efficient for Cs + over the other metal ions. These results also indicate that the selectivity of the metal ions for CBCBGA decreases with the decreasing size of the metal ions in the following order: Cs + > Rb + > K + > Na + . , …”
Section: Resultsmentioning
confidence: 59%
“…The partitioning of cesium ion from simulated high level liquid waste solution using 1,3-dioctyloxy calix[4]­arene-benzo-crown-6 has been earlier investigated by Kumar et al The high selectivity of Cs + ion over Na + ion with bis­(2-propyloxy)­calix[4]­crown-6 has been investigated by Ali et al The use of nitrobenzene as an organic diluent for the extraction of alkali metal ions using dibenzo-18-crown-6 has been reported by Makrlík et al Michael et al reported a theoretical study on the neat water–nitrobenzene liquid–liquid interface at 300 K. Chevrot et al studied the effect of dicarbollide anions on the separation of the highly hydrophilic Eu 3+ /Cs + cations by nitrogen-based bis-triazine-pyridine ligands to an octanol solution. The selectivity of Cs + and Na + ions in chloroform–water system was also performed by Muzet et al Kumar et al reported a new calix-benzo-crown-6 (CBCBGA) ionophore, which was found to be highly selective for the removal of Cs + ion over other metal ions from the acidic waste solution.…”
Section: Introductionmentioning
confidence: 91%
“…In this respect, the density functional theory (DFT) method is currently widely used 40,41 which is an appropriate level of calculation can comprehensively provide molecular level insights of the experimentally obtained results on the selective extraction processes by different ligand systems. For instance, Ali and coworkers 42 have reported an unusually high selectivity of Cs + in a calix-crown based ligand using DFT calculations. Similarly, Boda et al studied the selective binding of Cs + over Na + with a macrocyclic calix-bis-crown ether using DFT studies, whereby the calculated results correlate well with the experimental ndings.…”
Section: Introductionmentioning
confidence: 99%
“…Some separation techniques, such as ion exchange, solid-phase adsorption, solvent extraction, metal–organic frameworks, ionic liquids, and others, have been investigated. A few technical processes, cesium separation by calix-crown extraction, fission product extraction, universal extraction, caustic side solvent extraction, and so forth, were proposed to remove cesium from acidic or alkaline medium. Some macrocyclic derivatives of crown ethers and calix[4]­crowns were studied. They showed better supramolecular recognition for cesium through non-covalent bond interactions based on size-matching principle. The authors developed two technical processes, SPEC and GPSC, for cesium and/or strontium removal using macroporous/mesoporous silica-based molecular materials containing two kinds of different derivatives, calix[4]­arene-R14 and 4,4′,(5′)-di­( tert -butylcyclohexano)-18-crown-6. , The removal of Cs and/or Sr was achieved by extraction chromatography. The mechanism is different from conventional complexing agents or chelating ligands through coordination bond interactions. This provides a valuable pathway for Cs removal by application of calix[4]­crown-6 derivatives or relevant functional materials via host–guest supramolecular recognition.…”
Section: Introductionmentioning
confidence: 99%